Electrochemical and Spectrastudies of Some Sulfa Drug Azodyes and Their Metal Complexes in Aqueous Solution - Mabrouk, E.M.; Omary, Kh.A.Al; Omary, A.S.Al-; El-Mossalamy, E.H. (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
The electrochemical behavior of some azo compounds derived from sulfa drugs derivatives in B.R. buffer solutions of different pH containing 20 (v/v) ethanol was investigated at the mercury electrode using different techniques (DC,DPP,CV and Coulometry) to investigate the effect of medium on the electro reduction process and suggestion the electrode reaction mechanism. The obtained results denoted that these compounds were reduced undergo a single irreversible 4- electron polarographic wave in acid and neutral solutions which represent the cleavage of the N=N center to the amine stage, whereas in alkaline solution, two wave are obtained the second is 2-electron irreversible wave corresponding to the reduction ofCHO group to CH2OH. The DPP and CV data showed a single peak in solutions of pH< 8, whereas three peaks are in alkaline solutions. The dissociation constants of the investigated compounds were determined by using spectrophotometric and potentiometric methods. Also the metal – ligand formation constants were determined potentiometrically and found in the order Cu˃ Co˃ Ni ˃Zn.